Early-stage resectable non-small cell lung cancer in Hungary - Gabriella Gálffy; Réka Hécz; Réka Bujdosó; Eszter Gáspár; Réka Korompay; Judit Hoffer; Szilvia Szécsényi; Celia Blasszauer; Dániel Reibl; Erika Tóth; Krisztina Bogos; László Agócs; et al. (Pathology and Oncology Research)
This study provides a comprehensive analysis of early-stage resectable non-small cell lung cancer (NSCLC) in Hungary, investigating incidence rates, demographic trends, treatment patterns and survival outcomes. We used data from the National Health Insurance Fund (NHIF) spanning 2013–2022, and we analyzed 6,571 patients with available NSCLC histology and no metastasis, who underwent curative surgery within 6 months of diagnosis, and evaluated epidemiological trends and the use of neoadjuvant and adjuvant therapies. For the efficacy analysis, we narrowed the patient cohort to 5,494 patients diagnosed and treated between 2013 and 2019 with at least three-year follow-up data. Key endpoints included overall survival (OS) and disease-free survival (DFS), inferred via time to first subsequent therapy (TFST). Our results revealed a gradual decline in early-stage resectable NSCLC diagnoses, with a significant drop in 2020, likely linked to COVID-19 restrictions. Older age groups (66–75 years) represented a growing proportion of cases, reflecting shifting demographic trends. Among patients with EGFR mutations receiving EGFR tyrosine kinase inhibitor (EGFR-TKI) therapy, OS significantly improved compared to those not receiving EGFR-TKI therapy, who are assumed to have wild-type EGFR status (HR = 0.58 (95% CI: 0.47–0.72), p < 0.0001). These findings underscore the importance of early detection, comprehensive biomarker testing and targeted therapies in improving outcomes for resectable NSCLC patients. Future studies with extended follow-up and integration of broader clinical data, including staging and patient comorbidities, are warranted to optimize therapeutic strategies.